Small-Scale Irrigation Mapping (SSIM) as a tool for improving and validating irrigated area maps: contextual approach and lessons learnt in Burkina Faso - Chaix-Bar, Mathieu; Cinderby, Steve; Barron, Jennie (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Recent rapid expansion of private small-scale irrigation provides an opportunity to improve livelihoods and food security, but requires knowledge of where it is happening, in order to sustainably manage water use. Concerns are rising regarding the negative impacts of unchecked expansion of irrigation on downstream water quality and availability, particularly when using sub-optimal practices (de Fraiture et al. 2014; Domenech and Ringler 2013; Shah 2007). Therefore, for informed planning of potential sustainable irrigation expansion, policy makers and resource managers at the national level are interested in maps of the current extent of small-scale irrigation. Although several maps of irrigated areas have been produced for Burkina Faso, these maps, often of 250 meter (m), 300 m or 1 kilometer (km) resolution, are of too low resolution to account for scattered irrigation on areas smaller than 1 hae. Small-scale irrigation in Burkina Faso is typically carried out on individual plots of less than a quarter of hectare, with a small proportion on groups of fields no larger than one hectare, implying that existing maps are not reliably capturing the true extent and distribution of small-scale irrigation in the country.